1987
DOI: 10.2134/agronj1987.00021962007900010012x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Corn Growth, Yield, and Grain Moisture from Air Growing Degree Days and Residue Cover1

Abstract: Low spring soil temperatures commonly restrict the early growth of corn (Zea mays L.) in the northern Corn Belt. A quantitative assessment of the effects of tillage and residue management practices on soil temperature would improve tillage recommendations in this region. The effect of tillage and surface residue cover on seedbed soil temperatures and subsequent corn growth were studied at four sites in the northern Corn Belt that differed widely in soil characteristics including drainage, texture, slope, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 10 publications
5
82
1
1
Order By: Relevance
“…Greater growth of the rye cover crop at shorter termination-time intervals also leads to greater surface residue cover, which lowers soil temperatures and increases soil moisture (Dam et al 2005;Swan et al 1987). Lower soil temperatures directly slow corn germination, growth, and development (Kaspar et al 1990;Swan et al 1987Swan et al , 1996.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater growth of the rye cover crop at shorter termination-time intervals also leads to greater surface residue cover, which lowers soil temperatures and increases soil moisture (Dam et al 2005;Swan et al 1987). Lower soil temperatures directly slow corn germination, growth, and development (Kaspar et al 1990;Swan et al 1987Swan et al , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Lower soil temperatures directly slow corn germination, growth, and development (Kaspar et al 1990;Swan et al 1987Swan et al , 1996. In northern corn-growing areas, soil temperatures of residue-covered soils are usually well below optimum early in the growing season (Kaspar et al 1990;Swan et al 1987Swan et al , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases (especially cold humid climates), yield reductions observed in no-tillage system have been attributed to cooler soil temperatures (from residue cover) that reduce seed germination and seedling growth (Swan et al, 1987;Bradford & Peterson, 2000). The Ingram's believe that, in addition to providing a guide for controlled traffic, the 14 inch skip in the cover crop planting (centered on the cotton row) alleviates this potential problem.…”
Section: Tillage Systemmentioning
confidence: 99%
“…Toward the end of the study (April−May), there were a few cases (127,142,152,167 DAFT) where the undisturbed soil temperature exhibited trends that were lower than in the other tilled treatments, but differences were small (data not shown). It has been reported that soils in no−tillage systems exhibit cooler temperatures (vs. tilled soils), which can create seed germina tion and early stand development problems (Swan et al, 1987;Bradford and Peterson, 2000). However, it is important to note that in our study, "undisturbed" denotes lack of tillage during one overwintering period, rather than a long−term history of no−tillage.…”
Section: Soil Temperature and Watermentioning
confidence: 99%